Answer:
(f + g)(4) = 9
Explanation:
We have that:
f = {(-1,-3), (1,1),(2,3),(4,6)}
this means that:
f(-1) = -3
f(1) = 1
f(2) = 3
f(4) = 6
and we also know that:
g = {(-1,-1),(1,7),(4,3)}
hich means that:
g(-1) = -1
g(1) = 7
g(4) = 3
Now we want to find:
(f + g)(4)
For the general case of two functions f(x) and g(x)
(f + g)(x) = f(x) + g(x)
Then:
(f + g)(4) = f(4) + g(4)
and we know both of these values, so we can just replace them:
(f + g)(4) = f(4) + g(4) = 6 + 3 = 9
Then we get:
(f + g)(4) = 9